PENDAMPINGAN KELEMBAGAAN DESA DALAM PERBAIKAN DATA PENERIMA BANTUAN COVID-19 DI PEKON KOTABATU TANGGAMUS - Meilinda, Selvi Diana; Mulyana, Nana; Utami, Anisa (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The government's efforts to cope with the economic impact of a pandemic COVID-19 by way of giving social assistance to vulnerable populations were not going well and create new problems in the village. Kotabatu Village, Kotaagung Sub-district as a service partner has experienced various problems related to this, including many people who complain that they do not receive assistance, even though the economy is in bad shape due to the COVID-19 pandemic. After being traced, the data collection system for people who received assistance from the impact of COVID-19 was limited by a fast time. The irregularity of target recipients is also caused by the population data collection information system which still uses a manual system. As a result, it creates several obstacles for partners in the process of managing and processing population data, especially related to data mismatches. Constraints often occur especially during the data collection process Kotabatu villagers by members of the family, people moved, people died, people came, people were born, and the manufacture of letter testimony population. The solution to dealing with the problem of irregularity in targeting aid recipients in Kotabatu Village, by assisting partners in carrying out a data improvement system for COVID-19 beneficiaries, this is important considering the poor data collection system has a negative impact on the community and social assistance recipients affected by COVID-19 in Kotabatu village. The outputs of this service are activity videos, the journal Martabe (Journal of Community Service index sinta 4) which will be published in 2021 and articles that will be presented at the Unila LPPM scientific meeting.